Electrogenic transport of Na+/K+-ATPase incorporated in lipidic cubic phases as a model biomimetic membrane. (1st July 2019) - Zatloukalova, Martina; Nazaruk, Ewa; Bilewicz, Renata
Abstract: The transmembrane pump Na + /K + -ATPase was reconstituted within a model membrane-mimetic system of monoolein liquid-crystalline cubic phase (LCP). LCP consists of a curved lipid bilayer forming the walls of a network of aqueous channels providing the lipid environment for the hydrophobic part of Na + /K + -ATPase, with the aqueous channels enabling protein contact with the aqueous environment. Electrogenic ion transport by Na + /K + -ATPase was investigated by chronoamperometry (CA). The results of the electrochemical measurements were compared with the spectroscopic assay of the protein activity. The transient currents were recorded following application of potential steps to the LCP modified electrode. Na + /K + -ATPase embedded in the lipidic part of the cubic phase transports cations across the mesophase film. Moreover, the lack of Na + halted protein function because Na + ions are required to promote the enzyme switching to P-E2 conformation. A specific Na + /K + -ATPase inhibitor, ouabain, added to the solution decreased ion transport abilities of the protein. Small-angle X-ray scattering (SAXS) measurements showed that the structure of cubic phase with incorporated Na + /K + -ATPase before and after the chronoamperometry experiments remained unchanged, and that the observed difference in current flowing through the cubic phase film with and without the protein was due to Na + /K + -ATPase activity in this environment. Highlights: The transmembrane pump Na + /K + -ATPase was reconstituted in lipid cubic phase. Electrogenic ion transport of Na + /K + -ATPase in cubic phase was investigated by chronoamperometry. The ion transport decreased in the presence of ouabain – the Na + /K + -ATPase inhibitor.